Urban rights and sustainability in Latin-America. First steps towards urban justice operationalization - DAVILA, JAVIER ALONSO GOMEZ (Alanya Hamdullah Emin Pa?a ?niversitesi, 2019)
The following research is based on the affirmation that urban sustainability in developing regions, such as Latin America, is an impossible goal to be totally achieved, due to the circumstances of poverty, informality (slums), corruption, violence, among others that exist there. Therefore, the urban sustainability in the cities of this region has to be reached through survival efforts that seek to balance the existing inequalities (urban justice). So, the first step to take is to detect and measure those inequalities, in order to be able to take actions to eradicate or decrease them. To do that, urban rights were chosen to be used as measuring tools for those urban injustices. The research presents five priority urban rights contextualized to the Latin-American spatiality, called the Latin-American urban rights (right to a living place, right to the public space, right to alterity, right to mobility and accessibility, and right to good government practices and public policies), that were obtained after analyzing urban and social characteristics in different cities such as Santiago, Chile, Salvador de Bahía, Brazil, and Monterrey, México.Finally, a first proposal of operationalization of the Latin-American urban rights is presented, which was applied to a case study in the city of Monterrey, México, in order to prove the efficiency of the model.